Purchasing Power and Multidimensional Poverty in Nigeria - Atseye, Fidelis; Eba, Maxwell-Borjor Achuk (dialektika kontemporer, 2025)
The study investigated the relationship between purchasing power and multidimensional poverty in Nigeria using annual data obtained from World Development Indicator (WDI) Statistical Bulletin for 23 years (1999 – 2021). Adopting the Ordinary Least Square (OLS) regression technique. The study concluded that holding all explanatory variables constant multidimensional poverty will experience an increase of about 137 percent in Nigeria. From the results of the analyses and the observations obtained, the findings of this study shows that multidimensional poverty is significantly affected by purchasing power parity, inflation rate, and public expenditures. An increase in purchasing power parity and public expenditures decreases poverty, while an increase in inflation rate increases poverty. Conclusively, the findings of this study are consistent with previous studies that have found a significant relationship between multidimensional poverty and purchasing power. Hence, the study recommended among others that policymakers should consider implementing policies that increase purchasing power parity, such as increasing the minimum wage or implementing economic stimulus packages that benefit low-income communities.